Land Use Change and Rural Livelihood in Changing Climate in Semi-Arid Akko LGA, Gombe, Nigeria - Abu, D; O. Abu , G.; Mbaya, L. A. (Kashere Journal of Humanities, Management and Social Sciences, 2022)
This study examines land-use/land-cover (LULC) dynamics and farmers’ perception of climate change and their adaptation strategies in semiarid Akko towards sustainable rural livelihoods. LULC analysis was carried out to generate the static area of the land-cover classes while the extent of climate variability in the study area was established from archival temperature and rainfall data. Farmers’ survey was conducted in five farming communities of Akko with a sample of 150 farmers that were on their farms as at the time of the survey. The results of the study reveals high rate of conversion of woodland and shrub-land vegetation to farmland. It also shows that temperature is on the increase while the total annual rainfall has been on a decrease during the last 30 years. The result also shows that farmers understanding of climate change is related to decreasing annual rainfall amount, increasing temperature, early drying up of surface water sources, intermittent drought and drier environment, reduction in vegetal cover/deforestation, increasing incidence of flooding, decrease crop productivity, increased pest and disease infestation and reduction in the severity of harmattan season. Major adaptation strategies adopted by the farmers include growing of drought resistant crop varieties and early maturing crop varieties, organic, compost and inorganic fertilizer application, prayers for divine intervention, mixed cropping, among others. The findings revealed that farmers are increasingly engaging in off-farm sources of livelihood. Recommendations made based on the findings include making drought resistant crop varieties and fertilizers more affordable, provision of sustainable household alternative source of energy to reduce greenhouse gas emissions which accentuate climate change, increased access to extension services as well as adequate and timely dissemination of climate information to farmers.